Hemosiderosis of Central Nervous System: a case report of a rare and underdiagnosed disease (Research, Society and Development, 2021)
Superficial Siderosis (SS) of Central Nervous System is a rare disease characterized by the deposit of hemosiderin in the brain and spinal cord. Clinically, it is characterized by progressive sensorineural ataxia and deafness associated with injury of superior motor neuron. The diagnosis is made by magnetic resonance imaging (MRI) of the encephalon and spinal cord. The objective of the study is to report the case of a patient with characteristic elements of the syndrome, accompanied in a private medical clinic.